Trauma, stigma, and autism : developing resilience and loosening the grip of shame - Gates, Gordon S. (Gordon Stanley Peter), 1966- (London ; Philadelphia : Jessica Kingsley Publishers, 2019)
This book explores how stigma can cause trauma, providing guidance on how marginalised people can develop resilience to manage and heal from traumatic stigma. Gordon Gates draws on his experience as a crisis counsellor, philosophical research, and his lived experience of stigma, trauma and autism.
10. Self-Recovery and Emotional Reimagining; Part D: Critical Autism; 11. Sociophenomenal Diversity, Intuition, and the Politics of Interaction; 12. Autism, Authentic Expression, and Support; References; Subject Index; Author Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Stigma (Social psychology); Autism -- Psychological aspects; Resilience (Personality trait); Psychic trauma; Stereotypes (Social psychology); Stereotyping; Stigmatisation (Psychologie sociale); Autisme -- Aspect psychologique; Résilience (Trait de personnalité); Traumatisme psychique; Stéréotypes.; FAMILY & RELATIONSHIPS -- Life Stages -- General; PSYCHOLOGY -- Developmental -- General; PSYCHOLOGY -- Developmental -- Lifespan Development; PSYCHOLOGY -- General; Psychic trauma; Resilience (Personality trait); Shame; Stigma (Social psychology)